Reconstruction of Supervision and Legal Accountability for the Misuse of Post-Death Notarial Deeds in the Digital Notarial Administration System - Kartika Kartika; KMS Herman (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2026)
This study examines notarial deeds as authentic instruments that possess perfect evidentiary power and play an essential role in ensuring legal certainty for the public. Problems arise when a notary dies while the protocols and deeds they have created remain in circulation and continue to be used in various legal relationships. This situation creates a normative legal gap regarding accountability for the misuse of deeds after the notary’s death, particularly within a notarial administration system that is gradually transforming toward digitalization. Digitalization improves efficiency, accelerates document distribution, and expands access to notarial services, but it also increases risks of misuse, manipulation, and unauthorized use of deeds due to insufficient control mechanisms. The existing supervisory system, which is still focused on individual notaries, is unable to effectively address risks arising after the termination of office due to death, resulting in suboptimal legal protection for related parties. This study aims to analyze weaknesses in the post-death notary supervision and liability system and to formulate a reconstructed supervision and accountability model in the digital notarial administration system. The research employs a normative legal method with statutory, conceptual, and systematic approaches. The findings identify normative gaps, weak protocol supervision, and the absence of an integrated national digital system. The proposed reconstruction includes shifting liability from personal to institutional responsibility, establishing institution-based supervision, and developing a digital system equipped with authentication, audit, and access control mechanisms.